Diversity of twenty-three sweet corn (Zea mays L. saccharata) varieties in Indonesia - FARAH SAFIRA SALSABILA HERYANTO; DESTA WIRNAS; ARYA WIDURA RITONGA (Society for Indonesian Biodiversity, 2022)
Abstract. Heryanto FSS, Wirnas D, Ritonga AW. 2022. Diversity of twenty-three sweet corn (Zea mays L. saccharata) varieties in Indonesia. Biodiversitas 23: 6075-6081. One of the most well-known vegetables in Asian countries, including Indonesia. Improving superior sweet corn varieties is important in the face of increasing biotic or abiotic stresses and consumer preferences for agricultural products. Plant breeding programs rely on genetic variability and heritability information. Therefore, this study aimed to quantify the genetic diversity and heritability of 23 commercial sweet corn varieties in Indonesia. The study was conducted at the Leuwikoppo experimental field of the Department of Agronomy, Faculty of Agriculture, IPB University, Bogor, West Java, Indonesia, from August to November 2021. Twenty-three commercial sweet corn varieties (hybrid and open-pollinated) from Indonesia were planted in the field employing a randomized complete block design with 3 replications. Ear shelf life and green ear yield had a high genotypic coefficient of variation (GCV), whereas plant height, ear height, stalk length, 100-grain weight, total soluble solids, green ear shelf life, green ear weight, and ear weight had a moderate GCV. Stem diameter, leaf number, leaf length, leaf width, 50% days to tasseling and silking, anthesis, silking interval, ear length, ear diameter, ear length with the kernel, ear length percent with the kernel, kernel length, and kernel width had a low GCV. High genetic diversity was present among the trialed varieties, indicating their high potential for improvement.